"Literature, " Theory from the South and the Case of the São Paulo School. (23rd March 2018) - Helgesson, Stefan
Abstract : With methodological support in Reinhart Koselleck's notion of historical semantics, and an empirical focus on the Brazilian critic Antonio Candido (1918−2017), this article approaches "literature" as a layered concept that will always fail to function as that "plane of equivalence" that Aamir Mufti sees as an outcome of the Orientalist episteme. This failure is historical in the strongest sense; it derives from the condition that "history is never identical with its linguistic registration, " as Koselleck puts it. A concept will therefore, throughout its life span, always encompass a combination of persisting and new meanings. In this way, Candido and the São Paulo school of criticism that he was instrumental in forming can be read as a strong instance of "theory from the South" that exploits the malleability of the concept from within its historical situatedness and contributes thereby to the conceptual worlding of literature.